Réponses

Meilleure réponse !
2013-12-21T19:14:47+01:00
B=(2x-3)(5-x)-(2x-3)²
B=10x-2x²-15+3x-(4x²-12x+9)
B=10x-2x²-15+3x-4x²+12x-9
B=-6x²+25x-24
Merci bcq!!
Mais j'ai pas compris pk (4x²-12x +9) devient -9 en bas??
2013-12-21T19:23:55+01:00
B = ( 2x - 3 ) ( 5 - x ) - ( 2x - 3 )²
= 2x * 5 + 2x * (-x) - 3 * 5 - 3 * (-x) - [ (2x)^2 - 2 * 2x * 3 + 3^2 ]
= 10x - 2x^2- 15 + 3x - [ 4x^2 - 12x + 9 ]
= 10x - 2x^2 - 15 + 3x - 4x^2 + 12x - 9
= -6x^2 + 25x - 24
Mercii
Mais c'est quoi ^ stp
^2 = au carré
A daccord merci